Comparison of the Effects of Atorvastatin, Hyaluronic Acid and Oxidized Cellulose (Interceed) on Reducing Intestinal Adhesions Postoperative after Open Abdominal Surgery in Animal Models: effects of atorvastatin, hyaluronic acid and oxidized cellulose on intestinal adhesions - Morshedi, Mehdi; Bahramifar, Ali; Nabizadeh, Alireza (Iranian Journal of Pharmaceutical Sciences, 2019)
Abdominal adhesions are considered as an important problem in abdominal surgery. In this study we compared the effectiveness of atorvastatin, hyaluronic acid and interceed (oxidized cellulose) in prevention of postoperative intestinal adhesions. A total of 40 Wistar-albino rats were randomly divided into 5 groups: Group 1 (Sham); Group 2 (Control or Adhesion induction); Group 3 (Adhesion induction + hyaluronic acid); Group 4 (Adhesion induction + oxidized cellulose); and Group 5 (Adhesion induction + atorvastatin). A same experimental method of cecal abrasion and ligature was used to produce adhesions in all rats. Fourteen days after adhesions formation, animals were killed and adhesions were scored according to macromorphological characteristics and adhesion-carrying tissues under standard histologic examination. Inflammation,vascularization and fibrosis in granulation sites were graded in all samples. Adhesion scores in all experimental groups were slightly lower than control group. Group 3 had the lowest mean adhesions score (1.18 ± 1.24) based on surgeon observation. The mean of adhesion score in Group 3 (1.18 ± 1.24) was significantly lower than that in Group 4 (3.43 ± 0.53) (p=0.004). Group 5 showed the lowest mean adhesions score on pathological examination (5.62 ± 3.73). The mean of adhesion total score in Group 3 was slightly lower than that in other groups; however, this difference was not significant. Hyaluronic acid, oxidized cellulose, and atorvastatin are effective in treatment and prevention of intestinal adhesions during open abdominal surgery. Although hyaluronic acid was slightly more effective, further studies are needed to evaluate the effect of combination therapy with these agents.